I. Kant on the Elevated in Nature and Man - Žičkytė, Rūta (Problemos, 1982)
The link between the category of the elevated with the moral values of man, and with the postulates of materialistic outlook is observed in the article where the antinomy of an aesthetic judgement is understood as the expression of Kantian tolerance to different methods of interpreting reality, as the way of norming the relations of the given society. The above tolerance is found to disappear in the classical German philosophy that postulates the absolute as the only essence and the criteria of beauty. It is this interpretation of beauty that is criticized by the modern positivism which finds but the form to be the elevated and beautiful.